Analisis Kebutuhan E-modul Terintegrasi Nilai Imtaq Di SMAS YLPI Pekanbaru - Rika Deliana; Siti Robiah; Nurkhairo Hidayati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study aims to identify the need for an integrated e-module containing spiritual and moral values (IMTAQ) among teachers and students at SMAS YLPI Pekanbaru. The e-module is an electronic-based module accessible via computers or Android devices, containing text, images, and videos that incorporate elements of IMTAQ values. The research was conducted at SMAS YLPI Pekanbaru during the 2024 academic year using a descriptive qualitative research method. Based on interviews conducted by the researcher with biology teachers and 10 grade XI students at SMAS YLPI Pekanbaru, it was found that teachers had never used an e-module as a teaching medium and had not integrated IMTAQ values into the teaching materials they used. Data analysis revealed that both teachers and students at SMAS YLPI Pekanbaru require an e-module integrated with IMTAQ values.